Microstructure evolution and mechanical properties of ZK61 magnesium alloy fabricated via friction stir additive manufacturing - Yichen Xiao; Lei Shi; Chuansong Wu; Shengli Li; Ji Chen; Wenjian Ren (Journal of Materials Research and Technology)
Friction stir additive manufacturing (FSAM) is a novel solid-phase AM method which enables AM of Mg alloy components to achieve excellent mechanical properties. In this study, a high-strength laminated block of ZK61 Mg alloy was fabricated by the FSAM process. The microstructure evolution and mechanical properties were comprehensively studied. The microstructure in the additive zone of the Mg alloy component prepared by FSAM shows uniform and fine equiaxed grains with a size range of 2–6 μm. In the direction parallel to the traverse direction, a strong {0001} basal texture is formed. Microstructural studies were conducted respectively on the primary stirring zone (SZ), re-SZ, and reheating zone in the SZ. It is found that the degree of dynamic recrystallization in the secondary stirring region is more intense which can effectively refine the grains uniformly. The stratified tensile results show that the average ultimate tensile strength (UTS) of the uppermost additive zone can reach 320 MPa, exceeding the UTS of the base materials, which is 275 MPa. The UTS of the FSAM component in the horizontal direction can reach 265 MPa. Nevertheless, due to the high texture strength and increased anisotropy of the product, the average tensile strength in the building direction only reach 40% of that in the horizontal direction. The microhardness of the SZ is between 55 and 70 HV, slightly less than the hardness of the base metal. It reveals FSAM process is a promising method for AM of ZK61 Mg alloy.